Two type II IFN members, IFN-γ and IFN-γ related (rel), regulate differentially IRF1 and IRF11 in zebrafish. Issue 65 (June 2017) - Ruan, Bai Ye; Chen, Shan Nan; Hou, Jing; Huang, Bei; Laghari, Zubair Ahmed; Li, Li; Nie, Pin
Abstract: Two members of type II IFNs have been identified in fish, i.e. an IFN-γ gene as in other vertebrates and a unique IFN-γ related (IFN-γ rel) gene being solely present in fish. However, the signalling pathways involved in the down-stream signalling of type II IFNs in fish remains poorly described. In this study, the type II IFNs mediated IRF1 was investigated in zebrafish, and the true homologous gene of mammalian IRF1 in fish was revealed despite the report of so-called IRF1a and IRF1b in zebrafish. As revealed in overexpression analysis, zebrafish IFN-γ had a higher induction ability than IFN-γ rel in relation with the expression of IRF1. IFN-γ stimulated the expression level of STAT1a and also STAT1b, but they had opposite trends with the increase of time; enhancement of STAT1a waned after 12 h post injection of plasmids; whereas STAT1b expression increased continuously. Zebrafish IRF1 gene promoter contained several putative transcription factor binding sites, including GAS and NF-κB motifs. Luciferase assay revealed that the GAS site was essential in the IFN-γ triggered IRF1 expression. In contrast, IRF11 contained neither GAS nor NF-κB elements, and did not respond to IFN-γ induction. It is considered that STAT1a and STAT1b are structurally and functionally similar to STAT1α and STAT1β in mammal respectively, and that IRF11, although used to be nominated as IRF1a, is not the orthologue of mammalian IRF1, but IRF1b in zebrafish should be the orthologue. Highlights: IRF1 was conspicuously induced by IFN-γ in comparison with IFN-γ rel in zebrafish. GAS motif was indispensable to zebrafish IFN-γ triggered transcriptional activation of IRF1. Promoter activity and mRNA expression of IRF11 in zebrafish were not responsible to IFN-γ signalling. IRF1 and IRF11 in zebrafish showed difference in promoter elements, responses to IFN-γ, and organ/tissue expression.